2008
DOI: 10.1002/pbc.21654
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CTG triplet repeat expansion in leukemic cells and normal lymphocytes from a 14‐year‐old female with congenital myotonic dystrophy

Abstract: We describe a rare case of acute lymphoblastic leukemia in a 14-year-old female with congenital myotonic dystrophy manifested as mental retardation, extensive contractures of multiple joints of the lower extremities, and severe scoliosis. Because of the potential toxicity of chemotherapy and the patient's poor performance status, a modified chemotherapy regimen was administered. Analysis of the greatly expanded number of CTG repeats at the 3' untranslated region of DMPK gene showed that the number of repeats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
6
2
Order By: Relevance
“…Several reports have identified longer repeat expansions in tumoral cells than in nontumoral cells of DM patients; these larger expansions were thought to occur during cellular proliferation of tumoral cells. 30,31 We did not find a significant association between the presence of cancer and the number of CTG repeats in the DM1 patients with known length of CTG repeats.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Several reports have identified longer repeat expansions in tumoral cells than in nontumoral cells of DM patients; these larger expansions were thought to occur during cellular proliferation of tumoral cells. 30,31 We did not find a significant association between the presence of cancer and the number of CTG repeats in the DM1 patients with known length of CTG repeats.…”
Section: Discussioncontrasting
confidence: 58%
“… 16,18–26 The molecular mechanism of this DM‐associated carcinogenesis, however, remains uncertain; upregulation of the Wnt/β‐catenin pathway and/or alterations of the mRNAs encoding tumor suppressor genes or oncogenes have been proposed as possible etiologies 27–29 . It is unclear whether the length of the pathogenic expansion is associated with cancer risk in DM 30–32 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sub-analysis, however, we did not observe an association between leukocyte DNA repeat expansion size and tumor development in either DM1 or DM2 patients. Past studies of neoplasms from DM1 patients have found that tumors contained longer CTG-repeat expansions than adjacent normal tissue [2224]. The high degree of tissue mosaicism in DM1 patients may provide an explanation as to why the repeat expansion size measured in peripheral blood DNA is not associated with tumor development in DM patients [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that repeat expansion size may be a key de-terminant of cancer risk in this context, because nucleotide repeat expansions are longer in MMD patients compared with Huntington disease or fragile X patients, 32 and case reports have demonstrated longer nucleotide repeat expansion in tumor tissue from MMD patients compared with their normal tissue. 33,34 If proven true, we would expect that patients with type 2 MMD, who are known to have the longest repeat sizes, would have higher risk of cancer, a hypothesis that needs further investigation. The observed cancer risk differences between various repeat disorders might also be related to the precise repeat expansion location within the affected gene.…”
Section: Commentmentioning
confidence: 99%